Digital competency framework in digital technology towards future industrial revolution in Malaysia - Ismail, Asnidatul Adilah; Hassan, Razali; Ahmad, Azura (Universiti Teknologi MARA, Kedah, 2025)
This study aimed to identify the digital competency domains and elements essential for IT graduates in Malaysia and to develop a specialized digital competency framework for future graduates. A quantitative approach was used, involving surveys across five polytechnics for pilot research, followed by data collection from ten polytechnics, with results validated through confirmatory factor analysis (CFA). The study established a Digital Competency Framework for Polytechnic IT Graduates, comprising four domains: Personal Effective Competencies, Functional Competencies, Essential Competencies, and 4IR Competencies, encompassing 15 elements. The findings highlighted that two domains demonstrated a high level of digital competence, while one was at an average level. The research offers valuable insights into the digital competencies necessary for IT graduates and supports the development of an educational system better equipped to prepare students for the challenges of Industry 4.0 in Malaysia.